2014
DOI: 10.1111/add.12718
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the tobacco retail outlet environment on adult cessation and differences by neighborhood poverty

Abstract: Aims This study examined the impact of tobacco retail outlets on cessation outcomes over time among non-treatment-seeking smokers and assessed differences by neighborhood poverty and individual factors. Design Observational longitudinal cohort study using geospatial data. We used generalized estimating equations to examine cessation outcomes in relation to the proximity and density of tobacco retail outlets near the home. Setting Eight large Designated Media Areas across the U.S. Participants A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 39 publications
(52 reference statements)
4
76
1
Order By: Relevance
“…The NAICS list has been used previously for similar studies. 15 Third, these analyses were not able to distinguish between the impact of tobacco product availability in outlets and outlet advertising on young adult behaviors. However, this is a limitation for all studies of outlet density and proximity in countries and geographic areas where point-of-sale advertising is allowed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The NAICS list has been used previously for similar studies. 15 Third, these analyses were not able to distinguish between the impact of tobacco product availability in outlets and outlet advertising on young adult behaviors. However, this is a limitation for all studies of outlet density and proximity in countries and geographic areas where point-of-sale advertising is allowed.…”
Section: Discussionmentioning
confidence: 97%
“…8 Recent years have seen a growing interest in reducing tobacco availability via retail outlets, 9 along with growing evidence that the distribution of outlets may impact tobacco use behavior. Studies have found that outlet density is associated with increased cigarette smoking among youth, [10][11][12][13][14] while outlet proximity [15][16][17][18] is associated with reduced smoking cessation among adults. However, evidence examining the impact of outlets on cigarette smoking or use of other tobacco products among young adults is scarce.…”
Section: Original Investigationmentioning
confidence: 99%
“…[16][17][18][19] Proximity to tobacco retailers is associated with decreased success in tobacco use cessation, 20,21 although this may be true only in lower socioeconomic status neighborhoods. 22 Tobacco retailer density has been associated with smoking behaviors [23][24][25] and with youth initiation; 26 however, some findings are mixed. 21,25,27 There are both regional and local patterns of same-sex couple migration and neighborhood selection in the United States.…”
Section: Original Investigationmentioning
confidence: 99%
“…This is especially pertinent in our low-income, urban, safety-net Hispanic population -one historically susceptible to tobacco use. 32 Even as full regulations on advertising begin to take effect, continued exposure to e-cigarette marketing tactics may adversely influence perceptions of product safety and efficacy in smoking cessation. By providing culturally sensitive interventions that more effectively target vulnerable populations, we can increase education on safety and mitigate harmful usage.…”
Section: Resultsmentioning
confidence: 99%